To the question of oxidation on the surface of oxides: temperature- programmed oxidation of cyclohexanol - Brei, Volodymyr V.; Levytska, Svitlana I.; Prudius, Svitlana V. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2022)
Temperature-programmed reaction (TPR) method with mass spectrometric control of the products was used to study of cyclohexanol oxidation into cyclohexanone on individual and mixed oxides supported by γ-Al2O3 and silica gel. In the TPR profiles the temperature of a maximum rate of cyclohexanone formation varies from 125°C for MoO3/Al2O3 to 235°C for less active CuO/Al2O3. The catalytic activity of individual oxides decreases in the order MoO3/Al2O3> V2O5/SiO2 > Fe2O3/Al2O3 > Bi2O5/Al2O3 > TiO2/SiO2 ≈ СeO2/Al2O3 > TiO2/Al2O3 > SnO2/Al2O3. As "reactive" oxygen in our TPR experiment was supplied only from oxide lattice, oxide activity is determined by different energy of the surface Me – O bonds. The approach to search for mixed active oxides based on decreasing coordination number of O2- ions is proposed, that confirmed by the example of CuO-WO3/Al2O3 catalyst. The mixed supported oxides, especially CuOCrO3/Al2O3, CuO-MoO3/Al2O3, MoO3-SnO2/Al2O3 and Bi2O3–SnO2/Al2O3, are more active in С6Н12О + 1/2О2 → С6Н10О + Н2О oxidation. The synthesized CuO-CrO3/Al2O3 catalyst provides cyclohexanone formation without side cyclohexanol dehydration and can be used for the oxidation of ethylene glycol – methanol mixture into methyl glycolate. CuO-Cr2O3/Al2O3 with a spinel structure of CuCr2O4 ([CuO4] 6− tetrahedra, Cu2+ sp3-hybridization) is more active in cyclohexanol oxidation than CuO/Al2O3 with flat [CuO4] 6−squares, Cu2+ dsp2-hybridization. This is explained by the lower energy of Cu-O bonds at sp3-hybridization of Cu2+ ions.